Reframing Traditional Craft through Recognition and Certification: A Multidimensional Analysis of Ushikubi Tsumugi in Contemporary Japan - Wu, Xingchen (Advances in Social Sciences Research Journal, 2025)
This study examines the current state and potential revitalization of Ushikubi Tsumugi, a traditional silk textile produced in Shiramine, Hakusan City, Ishikawa Prefecture. Despite its designation as a national traditional craft, Ushikubi Tsumugi faces dual challenges: declining production and limited consumer engagement. The research adopts a three-pronged approach. First, it analyzes the institutional definitions and certification systems established by both the local producers’ cooperative and the Ministry of Economy, Trade and Industry. Second, it presents findings from an original survey targeting Ishikawa residents (n = 900), focusing on how identity attributes—such as gender, age, marital status, and occupation—influence recognition, ownership, emotional receptivity, and gift-giving intention. Third, it discusses how traditional crafts may be sustained through cultural branding and policy support. The results reveal a tension between institutional legitimacy and market accessibility. While emotional receptivity to Ushikubi Tsumugi is high—especially as a gift—ownership remains low, and willingness to give is cautious. The study concludes that reviving traditional industries requires not only technical preservation but also strategic adaptation. Recommendations include product diversification, improved distribution, cultural storytelling, and enhanced intergenerational engagement. These findings contribute to broader discussions on sustainable cultural heritage in contemporary consumer society.